Resurgence of Polymyxin B for MDR/XDR Gram-Negative Infections: An Overview of Current Evidence - Suneel Kumar Garg; Omender Singh; Deven Juneja; Niraj Tyagi; Amandeep Singh Khurana; Amit Qamra; Salman Motlekar; Hanmant Barkate (Critical Care Research and Practice)
Polymyxin B has resurged in recent years as a last resort therapy for Gram-negative multidrug-resistant (MDR) and extremely drug resistant (XDR) infections. Understanding newer evidence on polymyxin B is necessary to guide clinical decision making. Here, we present a literature review of polymyxin B in Gram-negative infections with update on its pharmacology.